Linear algebra with applications - Nicholson, W. Keith; BC Open Textbook Project; BCcampus (Lyryx, 2019)
"After being traditionally published for many years Linear Algebra with Applications by W. Keith Nicholson is now released as an open educational resource and part of Lyryx with Open Texts! Overall, the aim of the text is to achieve a balance among computational skills, theory, and applicationsof linear algebra. It is a relatively advanced introduction to the ideas and techniques of linear algebra targeted for science and engineering students who need to understand not only how to use these methods but also gain insight into why they work. The contents have enough flexibility to present a traditional introduction to the subject, or to allow for a more applied course. Chapters 1-4 contain a one-semester course for beginners whereas Chapters 5-9 contain a second semester course. The text is primarily about real linear algebra with complex numbersbeing mentioned when appropriate (reviewed in Appendix A)"--BC Campus website.
This bibliographic record is available under the Creative Commons CC0 "No Rights Reserved" license.
This work is licensed under the Creative Commons Attribution-NonCommercial-ShareAlike License.
"Base textbook."
Includes index.
Description based on online resource; title from pdf title page (viewed on February 22, 2019).
Keywords: Algebras, Linear -- Textbooks; Electronic books